Association between Th-17 cytokine profile and clinical features in patients with spondyloarthritis (2011)
In recent years, a substantial amount of information has become available on the relationship between cytokines associated with the Th-17 profile and the development of spondyloarthritis (SpA). The purpose of this study was to evaluate inflammation markers in serum and synovial fluid (SF) and levels of cytokines related to the Th-17 profile in patients with different subtypes of SpA and healthy subjects. We evaluated this cytokine profile in light of the clinical activity of the disease in 62 patients. Serum cytokine levels (IL-17, IL-6, IL-1 alpha, TNF alpha, IFN-gamma) were measured by flow cytometry. IL-23, serum amyloid (SAA) and metalloproteinase 3 (MMP-3) were measured with ELISA. In all patients, clinical evaluation was performed using the activity and function indexes of the disease. A comparison showed that IL-17, IL-23, IL-1 alpha, IL-6, and TNF-alpha levels were significantly higher in the serum of SpA patients than healthy subjects (HS), and there were no differences among SpA subtypes. In SF we found higher concentrations of cytokines, but only IL-23 showed significant differences (p<0.05). We found a relationship between enthesitis and peripheral involvement and serum IL-17 levels (9 to 63 pg / ml). There was a correlation between levels above 63 pg/ml and a history of infection. Higher levels of IL-23 in synovial fluid could suggest local amplification of the Th-17 cytokine profile. These results suggest a possible relationship between IL-17 and enthesis involvement in SpA.